Vaginal changes after ovariectomy in ewes: A large animal model for genitourinary syndrome of menopause - Vodegel, Eva V; Guler, Zeliha; Ras, Lamees; Mackova, Katerina; Groeneveld, Anne C H M; Bezuidenhout, Deon; Deprest, Jan; Jeffery, Stephen T; Roovers, Jan-Paul W R (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2023)
OBJECTIVE: To evaluate the effect of iatrogenic menopause on the physiology of the vagina of the ewe and to evaluate if vaginal changes in ewes can be translated to women with genitourinary syndrome of menopause (GSM). METHODS: Preclinical research with Dohne Merino ewes. Iatrogenic menopause was induced by bilateral ovariectomy (OVX). Animals were randomized for surgery, blinded for allocation and outcome assessment. Differences between groups were determined by linear regression analyses at 5 months after OVX. Outcome measures were vaginal epithelial thickness, pH, vaginal maturation value, vaginal maturation index, epithelial glycogen accumulation, content of elastin fibers, collagen, and vascularity. RESULTS: OVX ewes (n = 20) showed epithelial thinning of the vaginal wall from 146 μm to 47 μm (mean, P < 0.001). Furthermore, epithelial glycogen accumulation and vascularity of the vaginal wall significantly decreased (43% and 23%, respectively) as compared with the control group (no intervention; n = 5). No significant differences were found for other outcome measures. CONCLUSION: This study established the ewe as a suitable large animal model for GSM. Furthermore, the similar relevant outcomes in humans and ewes hold great value for future translational research for the evaluation and optimization of different treatment modalities for GSM.
Keywords: Sheep; Humans; Menopause; model; Glycogen; atrophy; genitourinary syndrome of menopause; Female; ovariectomy; lidé; modely u zvířat; zvířata; Vagina; vagina; ženské pohlaví; menopauza; ovarektomie; Models, Animal; Ovariectomy; iatrogenní nemoci; Animals; Iatrogenic Disease; glykogen; ewe; ovce